Longitudinal study of mandibular behavior in Class I subjects with vertical and horizontal growth - Dirceu Barnabé Raveli; Savana Maia; Luana Paz Sampaio; Denise Rocha Goes Landázuri; Taísa Boamorte Raveli (Dental Press Editora, 2012)
OBJECTIVE: To evaluate possible differences in mandibular behavior in Class I individuals with vertical and horizontal growth patterns. METHODS: The sample consisted of 20 untreated Class I individuals divided into: Group 1 comprising 10 individuals with vertical growth pattern and Group 2 comprising 10 individuals with horizontal growth pattern, all of them belonging to the Burlington Growth Center files, University of Toronto-Canada, radiographically followed-up at ages 9, 12 and 21. Cephalometric radiographs, determined mean values for a long-term evaluation of mandibular behavior using the following measurements: SNB, Co-GN, SN.GoMe, anterior facial height and posterior facial height. RESULTS: SNB and Co-Gn values were higher in horizontal growth group at all of the ages studied; SN.GoMe measure was significantly lower in horizontal growth group; anterior facial height (AFH) showed lower values in individuals with horizontal growth pattern; and posterior facial height (PFH) showed lower values in individuals with vertical growth pattern. CONCLUSION: Long-term comparisons of Class I individuals' growth tendencies indicate that there are significant differences between both groups. Mandible showed a trend to clockwise rotation in Group 1. Group 2 showed a trend to brachycephalic facial form, due to the deficit in vertical development with regard to anterior facial height. OBJETIVO: avaliar as possíveis diferenças no comportamento mandibular em indivíduos Classe I com crescimento vertical e horizontal. MÉTODOS: a amostra desse estudo consistiu de 20 indivíduos Classe I não tratados, sendo o grupo 1 composto por 10 indivíduos com padrão de crescimento vertical e o grupo 2 por 10 indivíduos com padrão de crescimento horizontal, pertencentes aos arquivos do Burlington Growth Center, University of Toronto, no Canadá, acompanhados radiograficamente nas idade de 9, 12 e 21 anos. Determinou-se, por meio de telerradiografias cefalométricas, em norma lateral, os valores médios para a avaliação longitudinal do comportamento da mandíbula utilizando as medidas SNB, Co-Gn, SN.GoMe, altura facial anterior e altura facial posterior. RESULTADOS: o valor de SNB e Co-Gn foram maiores no grupo com crescimento horizontal em todas as idades. A medida Sn.GoMe foi significativamente menor no grupo com crescimento horizontal, a altura facial anterior (AFH) apresentou valores menores nos indivíduos com padrão de crescimento horizontal, e a altura facial posterior (PFH) apresentou valores menores nos indivíduos com crescimento vertical. CONCLUSÃO: as comparações longitudinais das tendências de crescimento de indivíduos Classe I indicam que existe diferenças significativas entre os dois grupos. A mandíbula apresentou tendência à rotação horária no grupo 1. O grupo 2 exibiu tendência à característica de indivíduos braquicefálicos, na forma facial, devido ao déficit no desenvolvimento vertical na altura facial anterior.